1978
DOI: 10.1002/bip.1978.360170508
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra and structure of synthetic polytripeptides

Abstract: SynopsisA number of polytripeptides related to collagen, namely, (Gly-Pro-Pro),, (Gly-Pro-Hyp),, (Gly-Hyp-Hyp),, (Gly-Pro-Ala),, (Gly-Pro-Leu),, (Gly-Pro-Gly),, (Gly-Ala-Pro),, (GlyAla-Hyp),, (Ala-Pro-Pro),, and (Ala-Hyp-Hyp), were investigated by the methods of ir spectroscopy and hydrogen-deuterium kinetics. Strength and order of interpeptide hydrogen bonds of the polytripeptides in a triple-helical conformation were found to depend on the amino acid composition and residue sequence in the triplets. Correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…The amide A frequency for these structures is about 40-60 cm -~ higher thanthat for a-helices,/3-structures and random coils. It is suggested that a high-frequency shift might be due to the existence of weak hydrogen bonds [21,22,24]. As mentioned above, such hydrogen bonds in the watercarbonyl structure are the hydrogen bonds formed by glycine NH-groups and water molecules.…”
Section: Discussionmentioning
confidence: 95%
“…The amide A frequency for these structures is about 40-60 cm -~ higher thanthat for a-helices,/3-structures and random coils. It is suggested that a high-frequency shift might be due to the existence of weak hydrogen bonds [21,22,24]. As mentioned above, such hydrogen bonds in the watercarbonyl structure are the hydrogen bonds formed by glycine NH-groups and water molecules.…”
Section: Discussionmentioning
confidence: 95%
“…A large increase in amide A frequency occurs for triple-helix formation, as evidenced by a change in amide A frequency of 3323 cm-' for Z-( Gly-Pro-Pro),-OCH3 to 3359 cm-' for Z-( GlyPro-Pro),-OCH3 . 48 This high-frequency shift may be due to long hydrogen bonds, and the higher value stays relatively constant for n = 4-8.…”
Section: Spectroscopic Studies Using Peptides Associated Triple-helicalmentioning
confidence: 97%
“…As in the case of mineral analysis, information on protein structure is extracted from broad spectral bands consisting of component peaks resulting from the Amide I modes of various secondary structures by using a spectral resolution technique such as Fourier self-deconvolution, second-derivative spectroscopy, and difference FTIR spectroscopy [15,25,[36][37][38][39]76]. The major underlying bands and their assignments are summarized (Table 1).…”
Section: Collagen Maturity and Collagen Crosslinksmentioning
confidence: 99%